2022
DOI: 10.1186/s13046-021-02211-2
|View full text |Cite
|
Sign up to set email alerts
|

Lipid reprogramming induced by the TFEB-ERRα axis enhanced membrane fluidity to promote EC progression

Abstract: Background Estrogen-related receptor α (ERRα) has been reported to play a critical role in endometrial cancer (EC) progression. However, the underlying mechanism of ERRα-mediated lipid reprogramming in EC remains elusive. The transcription factor EB (TFEB)-ERRα axis induces lipid reprogramming to promote progression of EC was explored in this study. Methods TFEB and ERRα were analyzed and validated by RNA-sequencing data from the Cancer Genome Atla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Besides, the content levels of SM and Cer were also reduced. Notably, both SM and PC are important components of cell membranes, and the PC/SM ratio could reflect the fluidity of cell membranes ( Mao et al, 2022 ), which is closely related to the invasive and migrative capacities of tumor cells ( Li et al, 2021a ). Our results showed that the PC/SM ratio was reduced both in the TNBC cells and tissues ( Figure 6B ) and demonstrated that dandelion extract could impede cell membrane formation and reduce the cell membrane fluidity via disrupting the biosynthesis of PC and SM, ultimately leading the inhibition of TNBC cell growth and migration.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the content levels of SM and Cer were also reduced. Notably, both SM and PC are important components of cell membranes, and the PC/SM ratio could reflect the fluidity of cell membranes ( Mao et al, 2022 ), which is closely related to the invasive and migrative capacities of tumor cells ( Li et al, 2021a ). Our results showed that the PC/SM ratio was reduced both in the TNBC cells and tissues ( Figure 6B ) and demonstrated that dandelion extract could impede cell membrane formation and reduce the cell membrane fluidity via disrupting the biosynthesis of PC and SM, ultimately leading the inhibition of TNBC cell growth and migration.…”
Section: Resultsmentioning
confidence: 99%
“…After 24 h, the cells were collected. The luciferase activity in cells was examined using a dual-luciferase reporter gene system (Promega) [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…In 2018, it was proposed that ERRα is a key regulator of cell metabolism and plays an important role in gynecological endocrine-related tumors and energy metabolism ( 101 ). A knockout of ERRα can inhibit the invasion, metastasis, and angiogenesis of EC and promote apoptosis ( 83 , 102 ). Endogenous or exogenous inhibition of the expression and function of ERRα has obvious anticancer effects ( 82 ).…”
Section: Hif-1α and Errα Crosstalk In Cancer Especially In Endometria...mentioning
confidence: 99%